Studi Komunikasi Budaya Buruh Pemetik Teh di Desa Cikendung, Slawi - Rocki Prasetya Suharso; Suzy Azeharie (Koneksi, 2020)
Culture is an accumulative store of knowledge, experience, beliefs, values, attitudes, meanings, hierarchies, religions, time choices, roles, spatial relations, broad concepts and material objects or possessions that are needed and supported by people or generations. Tea pickers in Cikendung Village, Slawi have their own culture which made their identity. The research wanted to find out how the communication culture of the tea pickers and how their social institutions. Social institutions, which means a system of behavior and relationships that are centered on specific activities in the lives of community groups, in this study are even more specific to tea pickers in Cikendung Village. The institutions that were researched are kinship, economic, religious, and somatic. This research uses a phenomenological research method by using descriptive qualitative. The research data were obtained from successful interviews with three sources, direct observations, document studies and literature studies. One of the conclusions obtained from this research is tea picker use Jawa Ngoko language to show intimacy between them, while with the foreman and guests they use Jawa Krama language to show respect.Budaya merupakan simpanan akumulatif dari pengetahuan, pengalaman, kepercayaan, nilai, sikap, makna, hirarki, agama, pilihan waktu, peranan, relasi ruang, konsep yang luas dan objek material atau kepemilikan yang dimiliki dan dipertahankan oleh sekelompok orang atau suatu generasi. Buruh pemetik teh di Desa Cikendung, Slawi memiliki budaya sendiri yang menjadikan hal itu sebagai identitas mereka. Penelitian ini ingin mengetahui bagaimanakah komunikasi budaya buruh pemetik teh dan pranata sosial mereka. Pranata yang diteliti antara lain adalah kinship, economic institutions, religious institutions, dan somatic institutions. Penelitian ini menggunakan metode penelitian fenomenologi dengan pendekatan deskriptif kualitatif. Data penelitian diperoleh dari wawancara mendalam pada tiga narasumber, pengamatan langsung, studi dokumen dan studi kepustakaan. Salah satu kesimpulan yang didapat dari penelitian ini adalah buruh pemetik teh untuk menunjukan keakraban diantara mereka maka mereka pake jawa ngoko, sementara dengan mandor dan tamu menggunakan bahasa jawa krama untuk menunjukan rasa hormat.